Copper switch-off: European experience and practical considerations - Ilsa Godlovitch; Peter Kroon (WIK-Consult GmbH, 2020)
In the third quarter of 2020, WIK-Consult updated its previous study of 2018 on challenges and opportunities regarding the switch-off of copper telecommunication networks in Europe (and the consequent migration to fibre networks). For this review questionnaires and interviews with NRAs and stakeholders were organized in 10 relevant European countries. Conclusions consider possible implications for policy-makers and regulators. Since 2018, further progress towards copper switch-off has been made in Estonia and Sweden, which were already frontrunners. However, the pace of migration has still been slow in countries such as Spain and Portugal, even though fibre is widespread in these countries. Then there are countries with still limited fibre deployment like Germany, Poland and the UK where only recently attention shifted towards the investments required. France and the Netherlands have 'escaped' this last group as concrete plans have been implemented to achieve copper switch-off and fibre roll-out by the incumbents. In general, where FTTH has been widely deployed, considerable benefits could be gained by switching-off overlapping copper networks. For the operator these are reduced operational costs and an improved business case for its fibre roll-out and for the customer improved quality of service. Beneficial for the environment and society are the reduced CO2 emissions of fibre networks in relation to the data consumed. (...) – – Im dritten Quartal 2020 aktualisierte WIK-Consult eine frühere Studie von 2018 zu den Herausforderungen und Chancen der Abschaltung von Kupfer-Telekommunikationsnetzen in Europa (und der damit verbundenen Migration zu Glasfasernetzen). Dazu wurden Befragungen und Interviews mit nationalen Regulierungsbehörden und Interessenvertretern in 10 relevanten europäischen Ländern durchgeführt. Die Ergebnisse beinhalten mögliche Schlussfolgerungen für politische Entscheidungsträger und Regulierungsbehörden. Seit 2018 wurden in Estland und Schweden, die bereits Vorreiter waren, weitere Fortschritte in Richtung Kupferabschaltung erzielt. In Ländern wie Spanien und Portugal ist das Tempo der Migration jedoch nach wie vor langsam, auch wenn Glasfaseranschlüsse in diesen Ländern weit verbreitet sind. Dann gibt es Länder mit einem noch begrenzten Glasfaserausbau wie Deutschland, Polen und das Vereinigte Königreich, wo sich die Aufmerksamkeit erst vor kurzem auf die erforderlichen Investitionen verlagert hat. Frankreich und die Niederlande gehören nicht mehr zu dieser letzten Gruppe, da konkrete Pläne zur Abschaltung der Kupferleitungen und zum Glasfaserausbau durch die etablierten Betreiber umgesetzt wurden. Im Allgemeinen könnten dort, wo FTTH weit verbreitet ist, durch die Abschaltung überlappender Kupfernetze erhebliche Vorteile erzielt werden. Für den Betreiber sind dies verringerte Betriebskosten und eine verbesserte Rentabilität für seinen Glasfaserausbau und für den Kunden eine verbesserte Dienstqualität. Vorteilhaft für die Umwelt und die Gesellschaft sind die geringeren CO2-Emissionen von Glasfasernetzen. (...)
Additional information: For FTTH Council Europe
Keywords: 330